Simultaneous Percutaneous Interventional Treatment of Atrial Septal Defects and Pulmonary Valve Stenosis in Children Under the Guidance of Transoesophageal Echocardiography Alone: Preliminary Experiences - Lu, Xuning; Wen, Ping; Liu, Yuhang; Zhu, Quanwei; Wang, Ning (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate the efficacy and safety of a simultaneous percutaneous interventional treatment of atrial septal defect (ASD) and pulmonary valve stenosis (PS) in children under the guidance of transesophageal echocardiography (TEE) alone. Methods: Eleven children with ASD combined with PS who were treated at our hospital between March 2015 and March 2019 were recruited; there were 4 males and 7 females. Preoperative transthoracic echocardiography showed that all of the ASDs were patent foramen ovale, with a maximum diameter of 12.9±2.7 mm. The guiding principle of septal occluder selection is that the diameter of the occluder should be 2-4 mm more than the maximum diameter of the ASD. The pressure gradient across the pulmonary valve in PS was 54.7±5.8 mmHg, and a balloon with a diameter 1.2-1.4 times the diameter of the pulmonary valve annulus was used for dilatation. Effective dilatation was repeated 2-3 times. All children underwent ASD occlusion and PS balloon dilatation through the femoral vein under TEE guidance without radiation or contrast agents. The patients underwent PS balloon dilatation first, followed by ASD occlusion. The treatment effect was evaluated by TEE immediately after the procedure, and the patients were followed up regularly. Results: All of the patients underwent successful simultaneous ASD occlusion and PS balloon dilatation through the femoral vein under the guidance of TEE alone. The pressure gradient across the pulmonary valve immediately after the procedure was 21.2±1.8 mmHg (P<0.01). No shunt was detected at the atrial septum level. The patients were followed for 3.0±1.4 years after the procedure. The atrial septal occluders were in the normal position in all of the patients, and there was no arrhythmia, hemolysis or residual shunting. The pressure gradient across the pulmonary valve at 1 month after the procedure was 18.5±3.3 mmHg (P<0.01). Conclusion: Simultaneous percutaneous interventional treatment of ASD and PS in children under the guidance of TEE alone is not only safe and effective, but it avoids trauma caused by extracorporeal circulation and surgical incision and damage caused by X-ray and contrast agents. The surgical sequence was PS balloon dilatation first, followed by ASD occlusion.